2012
DOI: 10.1155/2012/972896
|View full text |Cite
|
Sign up to set email alerts
|

Multimodel GCM-RCM Ensemble-Based Projections of Temperature and Precipitation over West Africa for the Early 21st Century

Abstract: Reliable climate change scenarios are critical for West Africa, whose economy relies mostly on agriculture and, in this regard, multimodel ensembles are believed to provide the most robust climate change information. Toward this end, we analyze and intercompare the performance of a set of four regional climate models (RCMs) driven by two global climate models (GCMs) (for a total of 4 different GCM-RCM pairs) in simulating present day and future climate over West Africa. The results show that the individual RCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
89
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(108 citation statements)
references
References 49 publications
16
89
1
2
Order By: Relevance
“…Diallo et al 2012Diallo et al , 2013aHernán-dez-Díaz et al 2013;Nikulin et al 2012;Gbobaniyi et al 2013;Sylla et al 2013b). …”
Section: Precipitation Climatologymentioning
confidence: 99%
“…Diallo et al 2012Diallo et al , 2013aHernán-dez-Díaz et al 2013;Nikulin et al 2012;Gbobaniyi et al 2013;Sylla et al 2013b). …”
Section: Precipitation Climatologymentioning
confidence: 99%
“…Thus, the phenomenon above could be attributed to the difference in convective parameterization and land sur- face parameterizations, as well as parameterizations over the ocean between GCMs and RCMs. On the other hand, the discrepancies between the RCMs and the driving GCM indicate that the RCM projections are sensitive to local and regional processes and the corresponding methods incorporated in the model (Diallo et al, 2012;Saini et al, 2015).…”
Section: Change In Seasonal Cyclementioning
confidence: 99%
“…In addition, the typical grid box of GCMs (in the range of 100-400 km) is too coarse to account for land surface heterogeneities from vegetation, topography and coastlines, which are important for the physical response governing the local and regional climate change signal (Paeth et al 2006;Rummukainen 2010). Regional Climate Models (RCM) can potentially overcome this limitation; however, Diallo et al (2012) found mixed results in terms of RCMs improving the simulation of climate patterns compared to the driving GCMs.…”
Section: Introductionmentioning
confidence: 99%